Multiple Acantholytic Acanthomas in Junctional Epidermolysis Bullosa - Sota Itamoto; Ken Natsuga; Takashi Seo; Shota Takashima; Hideyuki Ujiie (Medical Journals Sweden, 2024)
Abstract is missing (Research letter)